2018
DOI: 10.1039/c8ra01093e
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pretreatment atmosphere of WOx/SiO2catalysts on metathesis of ethylene and 2-butene to propylene

Abstract: The effect of a gas pretreatment atmosphere (pure N 2 , pure H 2 and mixed H 2 /N 2 ) on the metathesis reaction between ethylene and 2-butene to propylene over calcined and non-calcined WO 3 /SiO 2 catalysts was investigated. The non-calcined catalysts exhibited higher activity than the calcined catalysts under different gas pretreatment atmospheres. The non-calcined catalyst with the use of pure H 2 pretreatment showed the highest catalytic performances. As revealed by various characterization results from N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 38 publications
(60 reference statements)
1
30
0
Order By: Relevance
“…Two absorption bands at 230 and 270 nm were observed in the spectra for all the catalysts (inset gure), whereas the adsorption bands between 400 and 800 nm were also observed for all the catalysts. According to the literatures, 8,15,17 the absorption bands at 230 nm could be assigned to isolated tetrahedral [WO 4 ] 2À species, while the absorption bands at 270 nm corresponded to octahedral polytungstate species. The adsorption bands between 400 and 800 nm could be assigned to W 4+ and W 5+ species.…”
Section: Structure Of Surface Tungsten Compoundsmentioning
confidence: 88%
See 4 more Smart Citations
“…Two absorption bands at 230 and 270 nm were observed in the spectra for all the catalysts (inset gure), whereas the adsorption bands between 400 and 800 nm were also observed for all the catalysts. According to the literatures, 8,15,17 the absorption bands at 230 nm could be assigned to isolated tetrahedral [WO 4 ] 2À species, while the absorption bands at 270 nm corresponded to octahedral polytungstate species. The adsorption bands between 400 and 800 nm could be assigned to W 4+ and W 5+ species.…”
Section: Structure Of Surface Tungsten Compoundsmentioning
confidence: 88%
“…In addition, these bands of the non-calcined catalysts were broader than the calcined catalysts, indicating that higher oxygen vacancies occurring on the WO 3 crystalline. 8 Considering the Raman band at 970 cm À1 of the calcined and non-calcined catalysts, it was found that this band of the non-calcined catalyst showed more obvious peaks than that of the calcined samples, indicating more isolated surface tetrahedral tungsten oxide species as also conrmed by the UV-Vis results. In addition, higher calcination temperature caused low intensity of the Raman band at 970 cm…”
Section: Structure Of Surface Tungsten Compoundsmentioning
confidence: 91%
See 3 more Smart Citations